2013
DOI: 10.1177/0954409713501654
|View full text |Cite
|
Sign up to set email alerts
|

Keeping track workers safe: a socio-technical analysis of emerging systems and technology

Abstract: Track maintenance work is one of the most hazardous jobs in the rail industry. Track workers are in danger of being fatally injured by rail traffic either on the track they are working on or on adjacent tracks. The rail industry has developed many safe working procedures and protection systems to minimise the risk. The Australian rail industry is now trialling new technology that automatically warns the track workers of approaching trains. These technologies may be added to or ultimately replace the current sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…Being aware of the problem (1), having a strong positive intention (6), and possessing the necessary knowledge and skills (5) to perform the required behavior (8) combined with experiencing no or limited environmental barriers (7) to doing so are considered necessary and sufficient to produce a safety-enhancing behavioral change among leaders (8). Attitudes (2: believing that the advantages of performing the new leadership behavior outweigh the disadvantages), social norms (3: perceiving more social pressure to engage in the leadership behavior than not to perform this behavior), and self-efficacy (4: leaders perceiving themselves to be capable of performing the leadership behavior under different circumstances) can weaken or strengthen a behavioral intention.…”
Section: Preparing Matrices Of Change Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Being aware of the problem (1), having a strong positive intention (6), and possessing the necessary knowledge and skills (5) to perform the required behavior (8) combined with experiencing no or limited environmental barriers (7) to doing so are considered necessary and sufficient to produce a safety-enhancing behavioral change among leaders (8). Attitudes (2: believing that the advantages of performing the new leadership behavior outweigh the disadvantages), social norms (3: perceiving more social pressure to engage in the leadership behavior than not to perform this behavior), and self-efficacy (4: leaders perceiving themselves to be capable of performing the leadership behavior under different circumstances) can weaken or strengthen a behavioral intention.…”
Section: Preparing Matrices Of Change Objectivesmentioning
confidence: 99%
“…A combination of factors affect rail worker safety. Previous studies have demonstrated organizational or technological risk management approaches through the management of safety rules [4] by introducing safe track maintenance schedules [5], tunnel monitoring systems to recognize and detect maintenance workers on the tracks or other technology solutions [6,7], or even digital twins for maintaining a safe working environment for track workers by reducing the time spent working in the danger zone [8]. Earlier research by Farrington-Darby and colleagues [9] identified 40 factors influencing the safety behavior and safety culture among railway maintenance workers, for example, supervisory presence, peer pressure, managers' communication methods, managers' accessibility and availability, the volume of paperwork, contradictory rules, and feedback messages from managers.…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…Alternatively, solutions as Automatic Track Warning Systems (ATWSs, [17]) can be exploited. When building an ATWS, it is evident that accurately knowing the location of the workers would help to raise the worker attention and improve its safety: for trackside maintenance workers, being struck by a train or a rolling stock can be fatal and only requires a momentary lapse in attention [17].Being able to accurately localize the worker in the red or green zone would have a significant impact on ATWS functionalities and on the consequent worksite safety. It should be remarked that any proposal of localization function for safety-critical devices must be compliant to the prescriptive safety standards of the railway domain.…”
Section: Application To the Railway Domain And Compliance With Standardsmentioning
confidence: 99%